Myocarditis Concurrent with Sweet Syndrome: A Presentation of Acute Myeloid Leukemia - Christopher G. Burkeen; David Pottinger; Chaitanya Iragavarapu; Reshma Ramlal; Gerhard Hildebrandt (Case Reports in Hematology)
Acute myeloid leukemia (AML) is the most common acute leukemia in American adults and portends a poor prognosis if untreated. Commonly, AML presents with symptoms related to concurrent leukopenia, anemia, or thrombocytopenia; however, due to its ability to affect many organ systems in the body, AML can have a highly varied clinical presentation. One such presentation is myocarditis, which is a rarely reported manifestation of AML. Myocarditis can have a varied clinical picture and often requires exclusion of other causes of cardiac dysfunction. Sweet syndrome, also known as acute febrile neutrophilic dermatosis, is another presentation of AML; however, it is more commonly associated with AML than cardiac involvement. Sweet syndrome can occur in patients with an already established malignancy or can occur de novo in a patient with previously undiagnosed cancer and, interestingly, can also be accompanied by extracutaneous manifestations, one of which is myocarditis. Herein, we report a case of a 45-year-old male with a history of obesity and depression who presented with chest pain, a tender and diffuse rash, and pancytopenia. Heart catheterization performed at outside institution was negative for coronary artery disease. Cardiac MRI images were compatible with myocarditis. Dermal biopsy of the rash was consistent with sweet syndrome. Peripheral blood flow cytometry and bone marrow biopsy confirmed the diagnosis of AML. He was treated with an induction chemotherapy regimen of 7 days of cytarabine and 3 days of daunorubicin with resolution of his chest pain and skin lesions. The patient had persistent leukemia cells on day 14 postinduction bone marrow biopsy and was treated with high-dose cytarabine reinduction treatment. Bone marrow biopsy with count recovery after reinduction therapy revealed complete response (CR).